2007
DOI: 10.1021/pr0702363
|View full text |Cite
|
Sign up to set email alerts
|

A Controversial Tumor Marker:  Is SM22 a Proper Biomarker for Gastric Cancer Cells?

Abstract: SM22, a dominant protein in smooth muscle cells (SMCs), has been widely reported to be abnormally expressed in many solid tumors. However, the expression patterns of SM22 are not consistent in all tumors, not even in the same ones. Whether SM22 should be considered a tumor biomarker is still debated in different laboratories. Herein, we have carried out a systematical investigation to validate SM22 expression in the primary tissues of gastric cancer (GC). Of eight cases, seven samples were found in the elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…(Table 1). These compounds were recognized by other authors as biomarkers of cancer disease [22][23][24][25][26][27][28][29][30]. However, this chromatogram is very complicated because the cells release a lot of VOCs and some of them are difficult to identify due to frail peaks separation or low detection limit (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 1). These compounds were recognized by other authors as biomarkers of cancer disease [22][23][24][25][26][27][28][29][30]. However, this chromatogram is very complicated because the cells release a lot of VOCs and some of them are difficult to identify due to frail peaks separation or low detection limit (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of bacteria may cause carcinogenic changes in the cells [21]; therefore, a lot of studies have been carried out for characterising substances in breath from patients with lung [22][23][24][25][26], breast [27] and gastric cancer [28][29][30]. It is known that the composition and quantity of VOCs in the exhaled breath from patient with lung cancer varies from healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al reported that SM22, a commonly used tumor marker in the past was actually a sign of neovascularization, and had been identified on the basis of contamination of tumor samples with vascular endothelial cells (37). To avoid this scenario, we took care in the present study, to conform 2-DE results using immunohistochemistry and tissue microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Qi et al and Ryu et al reported that SM22 was up-regulated in esophageal squamous cell carcinoma and gastric cancer, respectively. [26][27][28] Therefore, systematical investigations are needed to elucidate the expression and function of SM22 in various cancers.…”
Section: Discussionmentioning
confidence: 99%